2012
DOI: 10.1186/1556-276x-7-66
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of NiTiNb SMA wires under recovery stress or prestressing

Abstract: The recovery stress of martensitic shape-memory alloy [SMA] wires can be used to confine concrete, and the confining effectiveness of the SMA wires was previously proved through experimental tests. However, the behavior of SMA wires under recovery stress has not been seriously investigated. Thus, this study conducted a series of tests of NiTiNb martensitic SMA wires under recovery stress with varying degrees of prestrain on the wires and compared the behavior under recovery stress with that under prestressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…In civil engineering applications, SMAs can be exploited for their superelasticity or SME properties for example NiTiNb alloys [10][11][12]. Some demonstration projects do exist in this context [1,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In civil engineering applications, SMAs can be exploited for their superelasticity or SME properties for example NiTiNb alloys [10][11][12]. Some demonstration projects do exist in this context [1,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The developed recovery stress with the 3% prestrain is larger than the stress of 398 MPa, which corresponds to 3% strain in the SMA bar. The residual stress, which is the remaining stress after cooling to air temperature, is generally smaller than the stress of 398 MPa, as previous studies indicated (Choi et al, 2010a, 2012b). The prestress in the SMA bar due to the 5% strain is 444 MPa.…”
Section: Specimens and Test Setupmentioning
confidence: 67%
“…Suhail et al (2020b) showed that forward transformation temperatures follow a linear relationship with applied pre-strain that is, greater the applied pre-strain, greater in the shift in the forward transformation temperatures. Other studies (Choi et al, 2013;Li et al, 2003;Proft and Duerig, 1990) have shown that recovery stress not only depend on the chemical composition and transformation temperatures of an SMA but also only the level of pre-strain applied. Proft and Duerig (1990) showed that the recovery stress in NiTiFe (47%Ni, 50%Ti and 3%Fe (at.…”
Section: Introductionmentioning
confidence: 99%